Pengaruh Peningkatan Pengetahuan tentang Gizi Ibu Hamil terhadap Outcome Kehamilan di Kota Bengkulu, Indonesia: The Influence of Maternal Knowledge Increase about Pregnant Women's Nutrition on Pregnancy Outcomes in Bengkulu City - Suryani, Desri; Krisnasary, Arie; Pratiwi, Bintang Agustina; Yandrizal, Yandrizal (Universitas Airlangga, 2024)
Background: Poor maternal health knowledge indirectly affects pregnancy outcomes. According to previous research, as many as 65% of mothers with poor or below average understanding give birth to children with low birth weight (LBW). Maternal and infant health information is needed. Objectives: To determine the effect of increased maternal knowledge on pregnancy outcomes. Methods: This study used a non-randomized quasi-experimental methodology. The study was conducted in Bengkulu City from August 2023 to January 2024. This study involved pregnant women who lived in the working area of ​​Bengkulu City health centers (five health centers). This study examined education, knowledge, and pregnancy outcomes. Validity and reliability were verified using a questionnaire (0.969 Cronbach's Alpha). Pre- and post-tests were conducted before and one month after school. The dependent t-test assessed the impact of the intervention and the correlation test assessed pregnancy outcomes. Results: The average maternal knowledge before and after the intervention was 16.58 and 18.08. Pregnant women's understanding changed after the intervention (p-value=0.000). Increased maternal knowledge did not affect pregnancy outcomes (p-value=0.301). Conclusions: There was an increase knowledge of pregnant women after education provision, but this did not have an impact on pregnancy outcomes. Education about pregnancy nutrition is very necessary so that mothers have good knowledge and maintain their intake.